2012
DOI: 10.5649/jjphcs.38.751
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Capecitabine by Simple Suspension Method

Abstract: The simple suspension method has been developed for performing tubal administration by placing tablets or capsules in hot water (55 °C) and serially decaying/suspending them without crushing/opening them. However, the stability of a cardinal drug against the pH of the suspension and heat remains unclear. In this study, we examined the stability of an oral anti-tumor preparation, capecitabine tablets, against the pH of the suspension and heat. Initially, we assessed the stability of capecitabine tablets suspend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…11) Although there have been other reports on the stability of individual anticancer drugs with respect to pH, none have yet covered as many drugs as in this study. [12][13][14][15][16] The pH information obtained in this study will be useful for testing the stability of suspensions and for selecting dissolution solutions. Little changes in pH were observed before or after passage through the tube, suggesting that the drugs tested in this study were unaffected by the tube.…”
Section: Discussionmentioning
confidence: 99%
“…11) Although there have been other reports on the stability of individual anticancer drugs with respect to pH, none have yet covered as many drugs as in this study. [12][13][14][15][16] The pH information obtained in this study will be useful for testing the stability of suspensions and for selecting dissolution solutions. Little changes in pH were observed before or after passage through the tube, suggesting that the drugs tested in this study were unaffected by the tube.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cosuspending drugs such as aspirin [ 5 ], amlodipine besilate [ 6 ], and capecitabine [ 7 ] with MgO or other agents that increase the suspension pH reduces the amount of the principal agent in the suspension by degradation or other changes. With clopidogrel bisulfate, the amount of clopidogrel (molecular form) isolated from test solutions A and B was similar to the amount of clopidogrel bisulfate used to prepare the test solutions, and this indicates that formulating these test solutions caused no degradation.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] In these studies, all medicines tested were shown to be stable in each suspension when applied alone to the simple suspension method. With regard to concomitant suspensions with other medicine, chemical decomposition was observed for L-dopa, 2) aspirin 5) and capecitabine, 8) when suspended with an alkaline drug or under pH-altered conditions. The use of this method has been increasing in Japan, but its application to drugs that are susceptible to chemical hydrolysis, such as prodrugs, remains controversial.…”
Section: Introductionmentioning
confidence: 99%